Molecular diversity of myxomycetes associated with decaying wood and forest floor leaf litter - Ko T.W.K. (2014)
Denaturing gradient gel electrophoresis (DGGE) fingerprinting was used to assess the molecular diversity of myxomycetes from environmental samples (decaying wood and forest floor litter) collected at the Mushroom Research Centre in northern Thailand. Total genomic DNA was extracted directly from environmental samples on which myxomycetes were not apparent. Part of the small subunit ribosomal RNA gene (SSU rDNA) was amplified and DNA sequences analyzed. DGGE gels revealed up to 17 operational taxonomic units (OTU) from decaying wood and 10 OTU from forest floor litter samples, but only seven (wood) and six (litter) OTU could be re-amplified and/or sequenced. Based on results obtained with the BLAST analysis program, the species involved appeared to correspond most closely to Diderma saundersii, Didymium iridis, Stemonitis flavogenita and Hyperamoeba sp. strain W2i on decaying wood and to Diderma saundersii and Physarum didermoides on forest floor litter. Our results suggest that then PCR-DGGE can be used to obtain data on the presence of myxomycetes in their primary microhabitats without the need to observe the sporocarps of these organisms. As such the technique would seem to have considerable potentialfor contributing to a more complete understanding of my xomycete diversity and ecology in terrestrial ecosystems. © 2009 by The Mycological Society of America, Lawrence, KS 66044-8897.